Efisiensi Pengolahan Limbah Cair RS Pelamonia Makassar dan RSUD Syekh Yusuf Gowa Tahun 2017 - Abd Gafur (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah IX, 2019)
Each wastewater treatment plant has efficiency in each treatment, knowing the efficiency of wastewater treatment can be determined whether each stage or wastewater treatment unit of each hospital as required or not. This research is intended to compare the efficiency of wastewater treatment of Pelamonia Hospital Makassar and Syekh Yusuf Hospital Gowa on 2017. Type of research used in this research is observasional with descriptive approach. The sample in this research is liquid waste in the Inlet and Outlet hospital. The results showed in RS. Pelamonia produces parameters that do not meet the average BOD at the inlet point 337.02 mg / L, COD at the inlet point 480 mg / L and outlet point BOD 179.28 mg / L, COD at the outlet point 260mg / lakang in RSUD Syekh Yusuf was given an unqualified parameter of average BOD at the inlet point of 165.66 mg / L, at the outlet point 97.11 mg / L, COD at the inlet point 280 mg / L, and at the outlet point 220 mg / L. Efficiency of RS wastewater treatment. Pelamonia showed the average IPAL able to reduce the BOD content by 46.84% efficient enough, COD 45.84% efficient enough and the TSS content of 60.81% efficient. While efficiency of waste water treatment of RSUD Syekh Yusuf showed that average WWTP can reduce BOD content by 41,33% efficient enough, COD content 21,42% less efficient and TSS content 80% efficient. We recommend that researchers investigate other factors that affect the efficiency of wastewater treatment.